ANALISIS IMPLEMENTASI KURIKULUM MERDEKA PADA PELAJARAN PAI DI SDIT PERSADA BAYAT KLATEN - Yunita, Yunita; Muh. Wasith Achadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
There are four focuses of discussion in this research, namely the Merdeka curriculum in PAI learning in schools, the implementation of the Merdeka curriculum, the impacts and obstacles in its implementation as well as solutions to the implementation of the Merdeka curriculum in PAI learning. This type of research is qualitative with a phenomenological approach. This research aims to analyze how the Merdeka curriculum is implemented at SDIT Persada Bayat. The research subjects were the principal and Islamic Religious Education teacher at SDIT Persada Bayat. The results of this research show that the implementation of the Merdeka curriculum in Islamic Religious Education lessons has not yet run optimally. The obstacles felt in implementing the Independent curriculum in Islamic Religious Education lessons are the difficulty of educators in creating enjoyable and high-quality learning and determining appropriate themes and content in P5 activities. to suit students' interests and talents.